ANALISIS PENGARUH HALAL AWARENESS, HARGA, PENDAPATAN, DAN RELIGIUSITAS TERHADAP KONSUMSI SKINCARE LOKAL (STUDI PADA GEN-Z MUSLIM KOTA SURABAYA) - Wijanarko, Zhafarina Shabhati; Aminullah Achmad Muttaqin (Islamic Economics and finance in Focus, 2023)
As the times progress, many people are now starting to realize the importance of using halal products. Author see that there is a price variable gap in previous research on skincare consumption. In addition, previous research has never been done with Generation Z objects, and including the religiosity variable. So, in this study the author will examine whether halal awareness, price, income and religiosity factors can affect consumption of local skincare in terms of its suitability in Islamic consumption patterns. This research uses the Structural Equation Modeling (SEM) method with the Partial Least Squares (PLS) approach to develop a behavior model for local skincare consumption. The results of this study are that the price and income variables are influential but not significant. while the halal awareness variable and the level of religiosity have a positive and significant effect on local skincare consumption.